Efektivitas Metode Discovery Learning dalam Mengembangkan Kreativitas Anak Usia Dini di Taman Kanak-Kanak Genius Kids II Kota Bukittinggi - Nipras Aini; Yulsyofriend Yulsyofriend (Jurnal Family Education, 2022)
This study aims to determine how effective the discovery learning method is in developing early childhood creativity at Genius Kids II Kindergarten, Bukittinggi City. In this study using quantitative methods with quasi-experiments. The data collection technique is in the form of an action test. The data analysis technique is done by using statistics. Based on the results of the research conducted, it was stated that overall there was an increase in the control class scores of children pre-test 98 and post-test 124. Meanwhile, the average control class for pre-test was 9,8 and post-test was 12,4. In addition, there was an increase in creativity ability using the discovery learning method in the experimental group with a pre-test score of 100 and post-test 140. While the overall average for pre-test 100 and post-test was 140. In both classes the results of the research were the same- the same increased but the experimental class had a higher score than the control class. Based on these results, it can be concluded that there is a significant difference between the creative abilities of children in the experimental class and the control class, thus showing the use of discovery learning methods is very effective on the creative abilities of early childhood.